1989
DOI: 10.2337/diacare.12.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Performance and Counterregulatory Responses During Mild Hypoglycemia in Healthy Volunteers

Abstract: The effect of mild hypoglycemia on psychomotor performance and counterregulatory responses was studied among 12 healthy volunteers. Each volunteer received two modified hyperinsulinemic glucose clamps. One morning, plasma glucose was held constant at euglycemic levels (4.9 mM) for 95 min, and another morning, it was lowered over 35 min and then held constant at hypoglycemic levels (3.4 mM) for 60 min. A battery of psychomotor tests and a questionnaire assessing hypoglycemic symptoms were administered before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 19 publications
6
26
0
Order By: Relevance
“…In addition, performance in the Trail Making B Test and the Digit Symbol Test was impaired significantly during hypoglycemia. This is consistent with previous observations (9,11,12,17,22) and confirms that the degree of hypoglycemia achieved was sufficient to affect other domains of cognitive function.…”
Section: Tests Of Memorysupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, performance in the Trail Making B Test and the Digit Symbol Test was impaired significantly during hypoglycemia. This is consistent with previous observations (9,11,12,17,22) and confirms that the degree of hypoglycemia achieved was sufficient to affect other domains of cognitive function.…”
Section: Tests Of Memorysupporting
confidence: 93%
“…In addition to the memory tests, the Trail Making B Test and the Digit Symbol Test were also administered. These tests were used to confirm the effect of hypoglycemia on cognitive function, as has been shown in previous studies (9,11,12,17,22).…”
Section: Cognitive Function Testsmentioning
confidence: 96%
“…Our findings are reassuring in this respect and in agreement with others (Ogle et al, 1976;Van Rooy et al, 1985); 3-adrenoceptor blockers did not prolong reaction time during euglycaemia, and at a blood glucose of 2.5 mmol 1-1 had no additive effect over and above that of hypoglycaemia. However, four-choice reaction time is a psychomotor test and it is possible that tests measuring different aspects of cognition (Stevens et al, 1989) might have shown an adverse effect of 3-adrenoceptor blockers.…”
Section: Resultsmentioning
confidence: 99%
“…General intelligence is a key finding and theoretical construct in the psychometric structure of human abilities (16) and is an important influence on many everyday activities (17). Although some studies of acute hypoglycemia have shown a deterioration in aspects of intelligence in both patients with diabetes (7,18) and nondiabetic subjects (19,20), previous studies in humans have not included subtests that were designed specifically to measure aspects of nonverbal intelligence.…”
mentioning
confidence: 99%